Relationship of negative life events with depression and anxiety in nursing students: a moderated mediation model of resilience and gender - Xiaoli Ye; Guihong Yang; Wei Zhang; Loren Toussaint; Fangfang Zhao (BMC Nursing)
Abstract Background Compared to ordinary student in the same age group, nursing students experience notably higher rates of depression and anxiety. Negative life events (NLEs) and resilience were recognized as risk factors and protective factors, respectively. There is little literature on the complex interaction of these factors among nursing students. Objectives The study aims to explore the potential relationship of NLEs, resilience, and gender with symptoms of depression and anxiety among nursing students. Methods A cross-sectional design was used for this study. A total of 568 participants from three universities in East, South and North China were recruited. Data collection instruments included socio-demographic characteristics, the Patient Health Questionnaire-9, the Generalized Anxiety Disorder Scale, the 10-item Connor-Davidson Resilience Scale, the Adolescent Life Events Self-Rating Scale, and The Pittsburgh Sleep Quality Index. A moderated mediation model was used to analyze the data. Results NLEs and resilience significantly related to depression and anxiety (r = -0.289 ~ 0.454, all ps < 0.01). NLEs had a direct effect on depression (B = 0.251, p < 0.001) and anxiety (B = 0.307, p < 0.001). Analysis of mediating effects revealed that NLEs influenced depression (B = 0.02, 95% CI : 0.004–0.041) and anxiety (B = 0.019, 95% CI : 0.004–0.040) through resilience pathways. Additionally, gender was found to have a moderating effect on the direct association of NLEs with anxiety (B = -0.031, p < 0.05), with males showing a greater association. Conclusions The findings suggest that improving resilience may help break the relationship of NLEs with depression and anxiety in nursing students. Additionally, the mental health of male nursing students needs more attention.